2023
DOI: 10.1101/2023.03.27.534486
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuromolecular interactions guiding homeostatic mechanisms underlying healthy ageing: A view from computational microscope

Abstract: Ageing brain is associated with a slow drift in structural network properties over the lifespan accompanied by reorganization in neuromolecular interactions giving rise to changes in global functional markers. What are the guiding principles of the homeostatic mechanisms that maintain the desired performance of functional neural circuits and preserve brain health during healthy ageing? We hypothesize that an ageing brain alters two primary neurotransmitters, glutamate and γ -aminobutyric acid (GABA), responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…One crucial facet of brain plasticity lies in its ability to establish new connections [Murphy and Corbett, 2009] and adjust underlying biophysical parameters, such as neurotransmitter modulation [Saha et al, 2023], in response to damage in brain topology. This process is often referred to as the brain's neurocompensatory mechanism [Lövde ´n et al, 2010,Pathak et al, 2022, Petkoski et al, 2023, Saha et al, 2023.…”
Section: Age-related Neurocompensatory Mechanismmentioning
confidence: 99%
“…One crucial facet of brain plasticity lies in its ability to establish new connections [Murphy and Corbett, 2009] and adjust underlying biophysical parameters, such as neurotransmitter modulation [Saha et al, 2023], in response to damage in brain topology. This process is often referred to as the brain's neurocompensatory mechanism [Lövde ´n et al, 2010,Pathak et al, 2022, Petkoski et al, 2023, Saha et al, 2023.…”
Section: Age-related Neurocompensatory Mechanismmentioning
confidence: 99%
“…The ability to switch between coordination states is driven by the tendency of the dynamical system to traverse through multiple attractors (Haken, 1983 ; Bressler, 2002 ; Kelso and Zanone, 2002 ; Tognoli and Kelso, 2014 ), quantitatively captured by a mathematical measure, metastability (Tognoli and Kelso, 2014 ; Deco and Kringelbach, 2016 ). Reflecting the fundamental role of metastability, modeling studies have found it to be a signature of brain's dynamic core (Deco et al, 2017 ) and maximized in the resting state (Hellyer et al, 2014 ; Deco et al, 2017 ; Naskar et al, 2021 ; Saha et al, 2023 ). A plethora of studies further validate this claim by showing changes in metastability to accompany altered or disordered states of consciousness.…”
Section: Introductionmentioning
confidence: 99%